2015
DOI: 10.1371/journal.pgen.1005433
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous FGD3 Variant as Positional Candidate for Disproportional Tall Stature Accounting for a Carcass Weight QTL (CW-3) and Skeletal Dysplasia in Japanese Black Cattle

Abstract: Recessive skeletal dysplasia, characterized by joint- and/or hip bone-enlargement, was mapped within the critical region for a major quantitative trait locus (QTL) influencing carcass weight; previously named CW-3 in Japanese Black cattle. The risk allele was on the same chromosome as the Q allele that increases carcass weight. Phenotypic characterization revealed that the risk allele causes disproportional tall stature and bone size that increases carcass weight in heterozygous individuals but causes dispropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…Previous studies have reported that some disease-associated alleles are accompanied by a favorable effect on other economic traits in cattle [2729]. Meat from Japanese Black cattle is highly valued for its abundant marbling due to considerable intramuscular fat deposition [30, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that some disease-associated alleles are accompanied by a favorable effect on other economic traits in cattle [2729]. Meat from Japanese Black cattle is highly valued for its abundant marbling due to considerable intramuscular fat deposition [30, 31].…”
Section: Resultsmentioning
confidence: 99%
“…), and FYVE, RhoGEF and PH domain‐containing protein 3 ( FGD3 ; Takasuga et al . ). Regarding fatty acid composition, fatty acid synthase ( FASN ; Abe et al .…”
Section: Introductionmentioning
confidence: 97%
“…Because all syndecans have a common structure, according to the three different structural domains of SDC3, the site where the missense mutation occurred probably located in a large extracellular domain. The functional significance of this substitution is unknown, but we presumed this missense mutation may change the amino acid property and affect the encoded protein structure (31) As a result, numerous current studies on animal genomics are focused on the analysis of mutations located within economically important genes that could correspond to previously described quantitative trait loci (QTL) (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the past few decades have clearly shown that synonymous single-nucleotide polymorphisms (SNPs) do not produce altered coding sequences, and therefore they are not expected to change the expression and function of the protein in which they occur (32)(33)(34)(35). However, according to recent research, the synonymous SNPs can affect protein expression by alteration or increase in the stability of the mRNA (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%